Detection of Financial Distress in Air Transportation Companies Registered in BEI Before and During Covid-19 - Rayhana Aisyah; Dyah Mieta Setyawati (Jurnal Multidisiplin Madani, 2023)
Financial distress analysis aims to identify and analyze financial distress in air transportation companies listed on the Indonesia Stock Exchange before and during Covid-19 with two airlines in Indonesia with CMPP and GIAA issuer codes. The research method used is descriptive method with a quantitative approach. The data used is secondary data in the form of company financial reports as objects of research for the period 2016 to 2021. Data analysis uses the Altman Z-Score model with the formula for calculating four financial ratios. The results of the study show that before and during Covid-19, CMPP and GIAA issuers were in a position of financial distress or entered a distress zone with a Z-Score value of less than 1.10 (Z <1.10)